2015
DOI: 10.1186/s12944-015-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between the APOB XbaI and EcoRI polymorphisms and lipids in Chinese: a meta-analysis

Abstract: BackgroundNo previous meta-analysis was to report the association between the apolipoprotein B (APOB) XbaI and EcoRI polymorphisms and serum lipids in Chinese. We performed the study to investigate their potentially association.Methods and Results Studies in English and Chinese were found via a systematic search of Pubmed, Embase, CNKI and Wanfang databases. The dominant genetic model and random-effects model were used to pool data from individual studies. As a result, a total of 30 articles with 5611 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In combination with our findings, it is possible that the association between the rs693 polymorphism and CHD in Asians is mediated by increased atherogenic lipid levels (TG, TC and LDL-C) and/or decreased HDL-C levels caused by the T allele of the rs693 polymorphism, since hypertriglyceridemia, hypercholesterolemia and hypo-HDL cholesterolemia are all recognized risk factors for CHD. In the subgroup analyses stratified by the ethnicity of subjects, we found that the rs693 polymorphism was significantly associated with higher levels of TG, TC and LDL-C, but not HDL-C in Asians, which is consistent with the recent results obtained from another meta-analysis specifically on Asian Chinese [ 84 ]. The present meta-analysis also demonstrated a significant association between the rs17240441 polymorphism and higher levels of APOB, TC and LDL-C, which explains why the rs17240441 polymorphism was associated with a higher risk of CHD in recent meta-analyses [ 82 , 83 ].…”
Section: Discussionsupporting
confidence: 91%
“…In combination with our findings, it is possible that the association between the rs693 polymorphism and CHD in Asians is mediated by increased atherogenic lipid levels (TG, TC and LDL-C) and/or decreased HDL-C levels caused by the T allele of the rs693 polymorphism, since hypertriglyceridemia, hypercholesterolemia and hypo-HDL cholesterolemia are all recognized risk factors for CHD. In the subgroup analyses stratified by the ethnicity of subjects, we found that the rs693 polymorphism was significantly associated with higher levels of TG, TC and LDL-C, but not HDL-C in Asians, which is consistent with the recent results obtained from another meta-analysis specifically on Asian Chinese [ 84 ]. The present meta-analysis also demonstrated a significant association between the rs17240441 polymorphism and higher levels of APOB, TC and LDL-C, which explains why the rs17240441 polymorphism was associated with a higher risk of CHD in recent meta-analyses [ 82 , 83 ].…”
Section: Discussionsupporting
confidence: 91%
“…The literature has investigated the association between rs693 polymorphism and lipemic levels, and our results are in line with studies on the topic as the one from Niu et al (14), who reported a significant association between the SNP and elevated TC, LDL, and triglycerides levels. Although other studies found divergent results, with no association between the SNP and the lipemic profile of individuals (9,18,19), a meta-analysis supports increased TC, TG, and LDL levels among carriers of the T allele (30). The well-known genetic heterogeneity between populations and a gene-environment interaction may be at least partly responsible for inconsistencies observed in the literature, possibly attributable to intra-and inter-population differences in diet and lifestyle (11).…”
Section: Discussionmentioning
confidence: 94%
“…Hyperlipidemia, highlighting elevated LDL cholesterol levels, has been reported to be a contributor to cardiovascular disease. Plasma constituents are determined by a complex interaction between genetics and environment (29), and genetic variations have been closely related to lipid metabolism disorders and atherosclerosis pathogenesis (30). In this sense, one of the genes of particular interest is the APOB gene (and its polymorphisms) since its product plays an essential role in the metabolism of circulating lipoprotein particles (3).…”
Section: Discussionmentioning
confidence: 99%
“…Our study was in line with studies concluding that there was no relationship between XbaI polymorphism and lipid profile (Casillas-Muñoz et al, 2018), and this can be explained by non-exclusion of patients on lipid lowering medications. Although other studies had found divergent results, Gu et al, (2015) and Niu et al, (2017) reported a significant association between the XbaI SNPs and dyslipidemia in CAD patients. It is thought that genetic heterogeneity between populations and a gene-environment interaction may be responsible for observed variations in these findings, possibly due to intra-and inter-population differences in risk factors (Chen et al, 2016, Niu et al, (2017.…”
Section: Discussionmentioning
confidence: 88%